Students’ Perception of Using Islamic Material in English Grammar Teaching for Islamic Higher Education - Siswoyo Siswoyo; Fatma Yuniarti (Universitas Lancang Kuning, 2023)
The objective of this article is to investigate (1) the forms of students’ perception of using Islamic materials in teaching English grammar, (2) factors of having perception, and (3) the implication of using Islamic material in teaching English grammar. This article used qualitative research, which used 26 English students departments. The data were collected through questionnaires. The result of the study showed that the students have positive and more positive perceptions. These positive perceptions are because the Islamic material in teaching English grammar helps them remember Islamic teaching. It also makes them easy to understand the English grammar. Besides that, the students feel that the teaching and learning are more challenging. The implication of using Islamic material in teaching English grammar is that their motivation is increasing. Further research should be conducted using more respondents to make the result of the study more comprehensive.